Pengembangan Interaksi Sosial Melalui Bermain Ular Naga Pada Anak Kelompok B Usia 5-6 Tahun di PAUD Nusa Indah Desa Penyampak kecamatan Tempilang - Pratama, Henda (ICEJ : Islamic Childhood Education Journal, 2024)
Social interaction must be instilled from an early age. This is very import to do that children can interact and also does not cause to have difficulty when interacting and also does not cause children to have difficulty with other people. The aim of this research is to find out hoh to implement the development of social interaction through playing with dragons and to find out the results in developing social interaction through playing with dragon snakes in group B children aged 56 years at PAUD Nusa Indah Desa Penyampak Kecamatan Tempilang District. The research uses descriptive qualitative research in PAUD Nusa Indah Desa Penyampak Kecamatan Village, Tempilang Disrict. The data playing activitter in developing social interaction in children , interviews, and documentation of observations carried out by observing dragon snake playing activites. In developing social interactions in children, interview to find out more information in research. Data analysis used includes data reduction, data preparation, and drawing conlusions. The result of the research that playing dragon snakes developing social ineraction in PAUD Nusa Indah Desa Penyampak Kecamatan Village, Tempilang Disrict, before starting other activites, the teacher prepares a location and large field for playing dragon snakes, the teacher explains the rules when playing dragon snakes, the teacher conducts assessments on children. The results of a sample of children’s social interactions through playing with dragons in group in group B children PAUD Nusa Indah Desa Penyampak Kecamatan Village, include children being able to interact and communicate with their friends, manpo children being able when playing, Marapu children working together, children being able to obey the rules when playing and chidren wanting controlther emotions.